2021
DOI: 10.1002/er.6402
|View full text |Cite
|
Sign up to set email alerts
|

Reduced power degradation in bifacial PERC modules by a rear silicon oxide additive layer

Abstract: In this paper, we investigate the influence of silicon oxide (SiO x ) layer on the potential induced degradation (PID) of P-type monocrystalline PERC cells and modules. A SiO x layer was added between the aluminum oxide (AlO x ) and silicon nitride (SiN x ) layers on the rear side of PERC cells using a newly designed plasma enhanced chemical vapor deposition (PECVD) tool, MAiA from Meyer Burger. The performance of cells and modules with this AlO x + SiO x + SiN x stack was characterized by electrical breakdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…[32] The AlO x /SiN x stack enhances the passivation effect and protects the AlO x film from potential reactions with Ag paste during the firing process. [33,34] This stack has been extensively utilized in ntype silicon cells such as n-PERL and TOPCon, serving as the front surface functional layer.…”
Section: Alo X : the Key To The Industrialization Of Perc Cellsmentioning
confidence: 99%
“…[32] The AlO x /SiN x stack enhances the passivation effect and protects the AlO x film from potential reactions with Ag paste during the firing process. [33,34] This stack has been extensively utilized in ntype silicon cells such as n-PERL and TOPCon, serving as the front surface functional layer.…”
Section: Alo X : the Key To The Industrialization Of Perc Cellsmentioning
confidence: 99%
“…For that purpose, SiN x ARC having a higher RI can be used as more UV light can be absorbed, increasing the SiN x layers electrical conductivity. [ 53,129,174,175 ] Pingel et al have also demonstrated that SiN x ARC with higher RI shows better PID‐s resistance even in dark with an enhanced effect using thin and homogeneous layers. [ 28 ] A strategy to benefit from high RI without enhancing parasitic optical absorption [ 176 ] is to use a stack of SiN x layers.…”
Section: Pid‐impacting Factors and Limitation Solutionsmentioning
confidence: 99%
“…For instance, the incorporation of a SiO x layer between the AlO x and SiN x layers on the rear side of bifacial p ‐PERC cells significantly increases PID‐p resistance. [ 175 ] This is attributed to the higher breakdown voltage of the AlO x / SiO x / SiN x stack. Ma et al [ 178 ] have also demonstrated better PID resistance of bifacial p ‐PERC cells by inserting a SiO x normalN y layer into the SiN x / SiO x and SiN x / AlO x stacks on the front and rear sides, respectively.…”
Section: Pid‐impacting Factors and Limitation Solutionsmentioning
confidence: 99%